Gender and Sexuality in English Language Education: Focus on Poland - Pakuła, Łukasz; Pawelczyk, Joanna; Sunderland, Jane (British Council, 2015)
With a focus on Poland, Łukasz Pakuła, Joanna Pawelczyk and Jane Sunderland empirically explore gender and sexuality in relation to classroom interaction and textbooks in the primary and secondary English language classroom. Based on data from a range of classrooms, the book shows how gender stereotyping in textbooks has not disappeared, that heterosexuality is the only sexuality in evidence and that heteronormativity is salient. Importantly, though, through teacher- and student-talk and classroom interaction generally, these representations can be and are negotiated and challenged. The book also offers practical suggestions for teachers, educators and publishers to make the English language classroom a truly inclusive social space.
Keywords: EFL; English Language Education; gender and sexuality; language and gender; language and sexuality; Critical Discourse Analysis; education studies; gender w podręcznikach; seksualność w podręcznikach; hidden curriculum; safe spaces; heteronormativity; discourse analysis; inclusive education; equality in education; practical advice for teachers